PROTACs improve selectivity for targeted proteins - Lihua Liu; Xian Guan; Jiezhen Zhuo; Xifeng Wu; Xin Han (Acta Materia Medica)
Proteolysis targeting chimera (PROTAC) technology has emerged as a powerful tool in drug discovery that enables targeted protein degradation through a unique bifunctional approach. This review provides a comprehensive overview of PROTACs with a focus on recent advances in enhancing selectivity and therapeutic potential. We begin with an in-depth discussion of the structure and mechanism of PROTACs, comparing PROTACs to traditional small molecule inhibitors and exploring how PROTACs overcome limitations, such as drug resistance and targeting previously undruggable proteins. Key to this discussion is the concept of selectivity in PROTAC design, including optimization of E3 ligases and linker structures to improve target engagement and minimize off-target effects. The review also highlights the potential of covalent PROTACs in enhancing specificity and efficacy. Furthermore, various target classes for PROTAC development are explored, including epigenetic regulators (e.g., BET proteins and histone deacetylases), cell cycle and signaling pathway proteins (e.g., CDKs, BCL-XL, and p38 MAPK), receptor and kinase targets (e.g., EGFR and BRAF), and immune regulators (e.g., CREBBP and IRAK3). We discuss the implications of targeting these proteins for cancer and other diseases, emphasizing the promise of PROTACs in transforming therapeutic strategies. Finally, the review highlights ongoing challenges, such as optimizing pharmacokinetics and clinical validation, and provides future perspectives on the evolution of PROTAC technology.